Pembentukan Portofolio Optimal pada Saham Jakarta Islamic Index Menggunakan Model Indeks Ganda - Ulfa Zuliantika; Dewi Murni (Journal of Mathematics UNP, 2022)
Investment is a process of placing a number of funds at this time in the hope of making a profit in the future. But, the higher the expected return the higher the risk. To minimize the risk, investors can form optimal portfolio.The purpose of this research is to determine the composition and proportion of stocks that form the optimal portfolio and determine return and risk of optimal portfolio. The type is this research is applied research using secondary data. The data are stocks of Jakarta Islamic Index period August – November 2020. Index in this research is IHSG, DJIA and HSI. The method used is Multi Index Model. The result of this research is obtained composition 2 stocks to be made as the optimal portfolio, this is JPFA 59.3044% and SMGR 40.6956% with a value of expected return portfolio is 4.505013% and risk of portfolio is 2.028694%.